Meningkatkan Kemampuan Kognitif Anak Usia Dini Melalui Media Kotak Pintar Pada Kelompok A Di TK Dahlia Tanjung Priok - Hasanah, Lia Ulya; Priyanti, Nina Yuminar; Yuntina, Lily (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
From various issues that arise, the focus of this research is to enhance cognitive abilities in early childhood at TK DAHLIA. The improvement of cognitive abilities will be carried out through stimulation from learning activities using the smart box media. The smart box media is chosen as the stimulation method to enhance the mathematical abilities of early childhood. This research will only focus on one issue, namely the improvement of cognitive abilities through the smart box media. The subjects in the research are 10 early childhood children in group A who attend TK DAHLIA. The scope of this research is to analyze the impact of smart box media stimulation on the enhancement of cognitive abilities in early childhood group A at TK DAHLIA. From several models of Classroom Action Research (CAR) that have been presented, the researchers use the Classroom Action Research by Kemmis and McTaggart. The data collection techniques used are observation, interviews, and documentation. The success criteria in this research are that the improvement of cognitive abilities is at a percentage ≥ 75% reaching a score with the criteria of Meeting Expectations (ME). The results of the research show that the cognitive abilities of early childhood group A can be enhanced by using the smart box media. This is indicated by the average class results in the pre-cycle having a percentage of 33% (BB), cycle I having a percentage of 59% (MB), and in cycle II, there is an increase in the cognitive abilities of early childhood group A with a percentage of 83% (ME).